A three-dimensional spheroidal cancer model based on PEG-fibrinogen hydrogel microspheres. (January 2017) - Pradhan, Shantanu; Clary, Jacob M.; Seliktar, Dror; Lipke, Elizabeth A.
Abstract: Three-dimensional (3D) in vitro cancer models offer an attractive approach towards the investigation of tumorigenic phenomena and other cancer studies by providing dimensional context and higher degree of physiological relevance than that offered by conventional two-dimensional (2D) models. The multicellular tumor spheroid model, formed by cell aggregation, is considered to be the "gold standard" for 3D cancer models, due to its ease and simplicity of use. Although better than 2D models, tumor spheroids are unable to replicate key features of the native tumor microenvironment, particularly due to a lack of surrounding extracellular matrix components and heterogeneity in shape, size and aggregate forming tendencies. In order to address this issue, we have developed a 3D "tumor microsphere" model, formed by a dual-photoinitiator, aqueous-oil emulsion technique, for the encapsulation of cancer cells within PEG-fibrinogen hydrogel microspheres and for subsequent long-term 3D culture. In comparison to self-aggregated tumor spheroids, the tumor microspheres displayed a higher degree of size and shape homogeneity throughout long-term culture. In sharp contrast to cells in tumor spheroids, cells within tumor microspheres demonstrated significant loss in apico-basal polarity and cellular architecture, cellular and nuclear atypia, increased disorganization, elevated nuclear cytoplasmic ratio and nuclear volume density and reduction in cell-cell junction length, all of which are hallmarks of malignant transformation and tumorigenic progression. Additionally, the tumor microsphere model was extended for the 3D encapsulation and maintenance of a wide range of other cancer cell (metastatic and non-metastatic) types. Taken together, our results reinforce the importance of incorporating a biomimetic matrix in the cellular microenvironment of 3D tumor models and the influential effects of the matrix on the tumorigenic morphology of 3D cultured cells. The tumor microsphere system established in this study has the potential to be used in future investigations of 3D cancer cell-cell and cell-ECM interactions and in drug-testing applications.